Systematic Literature Review (SLR): Peran Lingkungan dalam Meningkatkan Keterampilan Siswa Berbahasa Indonesia - Khairani, Putri; Nisa, Sahrun (MASALIQ, 2024)
This research aims to evaluate the extent to which the environment influences an individual's language skills, particularly in Indonesian. The method applied is a Systematic Literature Review (SLR). Data were collected by documenting all articles with similar research. Six articles from Google Scholar were used as sources in this study. The results show that the environment plays a primary role in the development of children's language, including speaking, listening, reading, and writing skills. Additionally, the roles of teachers and parents are also crucial in enhancing children's language abilities.